Evaluation of adenoviral vector Ad19a encoding RSV-F as novel vaccine against respiratory syncytial virus - Fuchs, Jana; Hübner, Julian; Schmidt, Anna; Irrgang, Pascal; Maier, Clara; Vieira Antao, Ana Isabel; Oltmanns, Friederike; Thirion, Christian; Lapuente, Dennis; Tenbusch, Matthias (npj Vaccines, 2024)
Respiratory syncytial virus (RSV) is the leading cause of severe lower respiratory tract infections in infants and toddlers. Since natural infections do not induce persistent immunity, there is the need of vaccines providing long-term protection. Here, we evaluated a new adenoviral vector (rAd) vaccine based on the rare serotype rAd19a and compared the immunogenicity and efficacy to the highly immunogenic rAd5. Given as an intranasal boost in DNA primed mice, both vectors encoding the F protein provided efficient protection against a subsequent RSV infection. However, intramuscular immunization with rAd19a vectors provoked vaccine-enhanced disease after RSV infection compared to non-vaccinated animals. While mucosal IgA antibodies and tissue-resident memory T-cells in intranasally vaccinated mice rapidly control RSV replication, a strong anamnestic systemic T-cell response in absence of local immunity might be the reason for immune-mediated enhanced disease. Our study highlighted the potential benefits of developing effective mucosal against respiratory pathogens.
CRIS-Team Scopus Importer:2024-11-15